Pemikiran Manajemen Pendidikan Islam Masa Rasulullah Saw Periode Madinah: Strategi, Materi Dan Lembaga Pendidikan - Madaniyah; Muhammad Syaifuddin (Hikamatzu | Journal of Multidisciplinary, 2024)
This study discusses the thoughts on Islamic education management during the time of the Prophet Muhammad SAW in the Medina period, focusing on strategies, materials, and educational institutions. The Prophet Muhammad developed an educational strategy centered on Islamic moral values ​​and sharia, accompanied by a practical approach to learning through mosques and halaqah. Educational materials include the Qur'an, religious knowledge, and life skills that are relevant to the needs of the community. Educational institutions at that time, such as the Nabawi Mosque, became centers of learning that supported the intellectual and spiritual development of the community. This thinking became the foundation for the development of a comprehensive Islamic education system to this day.